Financialisation, ownership and employee interests under private equity at the AA, part two. Issue 3 (2nd May 2016) - Clark, Ian
Abstract: This article examines a theoretically informed case study of the effects of financialisation at the workplace. It focuses in particular on trade union de‐recognition and trade union recognition in the furtherance of ownership interests. The paper reports on the continued diffusion of investor‐owner interests under the private equity business model which has recently witnessed the AA re‐listed on the stock market. It addresses two research questions. One, how are investor‐owner interests secured by trade union de‐recognition and re‐recognition? Two, how and why, as a de‐recognised trade union, does the GMB continue to campaign for and represent GMB members in the AA when the IDU (the independent democratic union) has sole recognition at the firm?